Hábitos alimentarios asociados a la malnutrición de adultos mayores. Unidad Vida para Todos. parroquia Santiago. diciembre 2022-abril 2023 - Tenelema Sisa, Darío Paul (2023)
Malnutrition in older adults is due to a combination of factors, including decreased physical activity, physiological changes, and impaired ability to absorb and utilize nutrients. In addition, eating habits can be affected by socioeconomic, cultural, and psychological factors. The present research aims to determine the eating habits associated with malnutrition in older adults attending the Life for All Unit located in Santiago parish, Guaranda canton, period December 2022-March 2023. A cross- sectional descriptive study was applied with a quantitative approach. The population consisted of 45 older adults who met the inclusion and exclusion criteria. That 41 of the older adults have low weight and 4 older adults have normal weight. A closed questionnaire was used as an instrument. As a result, most of the older adults presented a nutritional condition of low weight, their consumption of vegetables is variable, fruits are consumed mostly once a week, which is essential to maintain a healthy and balanced diet, likewise, they consume dairy products and meats that provide essential nutrients for health. Most of them do not eat junk food, fat and the most consumed oil by the elderly is soybean oil. It is important to mention that they live with their relatives and do not have money to buy food, which influences malnutrition. They do not engage in physical activity because they do not have enough time. The study concluded with the design of a counseling guide for nurses and health promoters based on Marjory Gordon's functional patterns to improve the nutritional health of the population's older adults. The implementation of this guide is to improve the quality of life of older adults in Santiago Parish. Keywords: Eating habits, Malnutrition, Older Adults